Non-invasive Brain Stimulation for Neuropathic Pain After Spinal Cord Injury: A Systematic Review and Network Meta-Analysis - Li, Lingling; Huang, Hailiang; Yu, Ying; Jia, Yuqi; Liu, Zhiyao; Shi, Xin; Wang, Fangqi; Zhang, Tingting (Frontiers in Neuroscience, 2022)
Objective: To systematically evaluate the effect of non-invasive brain stimulation (NIBS) on neuropathic pain (NP) after spinal cord injury and compare the effects of two different NIBS. Methods: Randomized controlled trials (RCTs) about the effect of NIBS on NP after spinal cord injury (SCI) were retrieved from databases of PubMed, Embase, Cochrane Library, Web of Science, CNKI, Wanfang Data, VIP, and CBM, from inception to September 2021. The quality of the trials was assessed, and the data were extracted according to the Cochrane handbook of the systematic review. Statistical analysis was conducted with Stata (version 16) and R software (version 4.0.2). Results: A total of 17 studies involving 507 patients were included. Meta-analysis showed that NIBS could reduce the pain score (SMD=-0.84, 95%CI -1.27~-0.40, P=0.00), the pain score during follow-up (SMD=-0.32, 95%CI -0.57~-0.07, P=0.02), the depression score of the NIBS group were not statistically significant than that of the control group (SMD=-0.43, 95%CI -0.89~0.02, P=0.06). Network meta-analysis showed that the best probabilistic ranking of the effects of two different NIBS on the pain score was repetitive transcranial magnetic stimulation (rTMS) (P=0.62)＞transcranial direct current stimulation (tDCS) (P=0.38). Conclusion: NIBS can relieve NP after SCI. The effect of rTMS on NP is superior to that of tDCS. We suggest that rTMS parameters are 80%-120% resting motion threshold and 5-20 Hz, while tDCS parameters are 2 mA and 20 min. However, it is necessary to carry out more large-scale, multicenter, double-blind, high-quality RCT to explore the efficacy and mechanism of NIBS for NP after SCI.